The Influence of Storage Duration and Elevation of Storage Temperature on the Development of Berry Split and Berry Abscission in Vitis vinifera L. cv. Thompson Seedless Table Grapes - Burger, D.A.; Jacobs, G.; Huysamer, M.; Taylor, M.A. (South African Journal of Enology and Viticulture, 2017)
Thompson Seedless grapes, packed in non-perforated low density polyethylene bags, were cold stored at -0.5°C and RH 83% for 0, 1, 2, 4 and 8 weeks. After storage at -0.5°C for these periods, the grapes were stored for another 2 or 5 days at -0.5°C , or the grapes were transferred and stored at 10°C and RH 88% for 2 or 5 days. The polyliners were kept closed during the different storage periods. Fruit quality examinations were conducted after the specified periods at -0.5°C, and after each additional 2 and 5 days at both temperatures. Berry split increased with prolonged storage at -0.5°C. A linear function (y = 0.58x - 1.14; R2 = 0.97) described this increase in berry split over 61 days storage at -0.5°C. Transferring the grapes from -0.5°C to 10°C resulted in a further increase in berry split. Grapes stored for 0, 1, 2 and 4 weeks at -0.5°C followed by 5 days at 10°C, showed a significant increase in berry split, compared with grapes stored only at -0.5°C for the same period. Although significant differences in berry abscission occurred, no definite trend was observed that could be ascribed to storage period at -0.5°C or to an elevation in storage temperature from -0.5°C to 10°C.